Welder's Anthrax: A Tale of 2 Cases. (17th October 2022) - Hendricks, Katherine; Martines, Roosecelis Brasil; Bielamowicz, Hannah; Boyer, Anne E; Long, Stephen; Byers, Paul; Stoddard, Robyn A; Taylor, Kathryn; Kolton, Cari Beesley; Gallegos-Candela, Maribel; Roberts, Christine; DeLeon-Carnes, Marlene; et al.
Abstract: Bacillus anthracis has traditionally been considered the etiologic agent of anthrax. However, anthrax-like illness has been documented in welders and other metal workers infected with Bacillus cereus group spp. harboring pXO1 virulence genes that produce anthrax toxins. We present 2 recent cases of severe pneumonia in welders with B. cereus group infections and discuss potential risk factors for infection and treatment options, including antitoxin.